2018
DOI: 10.5114/hm.2018.76081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of self-management education versus quadriceps strengthening exercises on pain and function in patients with knee osteoarthritis

Abstract: Purpose. To investigate and compare the effects of 6-week self-management education (SME) and quadriceps strengthening exercises (QSE) on pain and disability in individuals with knee osteoarthritis (OA). Methods. A total of 79 (13 males, 66 females) consecutive patients with knee OA were randomised into SME and QSE groups. The SME group were taught modules of self-management once a week for 6 weeks, while the QSE group had supervised QSE thrice a week for 6 weeks. Pain intensity and physical function were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Quadriceps strengthening exercises (QSE) The QSE program was created after a literature review [22,23], clinical practice, and consultation with experts. It has been shown to be safe, effective, and straightforward for study participants.…”
Section: Interventionsmentioning
confidence: 99%
“…Quadriceps strengthening exercises (QSE) The QSE program was created after a literature review [22,23], clinical practice, and consultation with experts. It has been shown to be safe, effective, and straightforward for study participants.…”
Section: Interventionsmentioning
confidence: 99%
“…Coleman et al showed that the execution of an SM program decreased the pain and increased the QOL and function of the patients (43). Moreover, Egwu et al indicated that the implementation of an SM program could reduce the pain of the patients (48). Furthermore, in the study by Mortazavi et al, which included six sessions of SM training, the execution of this intervention led to a decrease in the disability of patients with KOA (35).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Egwu (2018) The results showed that supervised Quadriceps Strengthening Exercise and Self-Management Education were both effective in reducing pain and disability in knee osteoarthritis but the improvement in results was better maintained with Self-Management Education. The significant difference between pain measures before and after exercise is because this increase in quadriceps muscle strength breaks the pain cycle by reducing muscle spasms, increasing muscle strength and increasing circulation, which reduces metabolic concentration.…”
Section: The Effect Of Quadriceps Strengthening Exercise On Muscle St...mentioning
confidence: 99%